IMPROVEMENT IN THE PACKAGING PROCESS OF CHOCOLATE BARS BY AUTOMATING THE PROCESS WITH LABVIEW IN PERU - AIRE-VALENCIA, JHONNY (2024)
THIS RESEARCH DESCRIBES THE DESIGN AND SIMULATION OF A PILOT PLANT APPLIED TO THE PACKAGING OF CHOCOLATE BARS, WHERE VARIOUS INSTRUMENTATION EQUIPMENT IS USED FOR THE MEASUREMENT OF PHYSICAL VARIABLES SUCH AS TEMPERATURE, FLOW AND LEVEL, WHICH INTERACT EACH OTHER IN THE 3 THREADS THAT HELP IN THE AUTOMATION OF THE EQUIPMENT THAT IS DEVELOPED ACCORDING TO THE CURRENT NEED OF SMES IN PERU. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.